Development and evaluation of a school-based bullying prevention program (Bullying&You): study protocol for a cluster randomized trial - Jantzer, Vanessa; Neumayer, Franziska; Lerch, Stefan; Kaess, Michael (Trials, 2025)
Bullying victimization affects one in ten schoolchildren in Europe and has far-reaching negative consequences for mental health and school achievement. Although school-based bullying prevention programs seem overall capable of reducing the frequency of bullying, the continuous development, improvement, and rigorous evaluation of bullying prevention programs with enhanced feasibility and efficacy is critical. Consequently, we developed the program Bullying&You, which applies a blended-intervention approach to school-based bullying prevention based on latest empirical knowledge regarding effective program components and program-related facilitators. We aim to test its efficacy within a cluster randomized trial (CRT).
Online veröffentlicht: 31. März 2025
Gesehen am 15.10.2025